Pengaruh Struktur Modal, Kebijakan Deviden Dan Cash Holding Terhadap Nilai Perusahaan - Pratiwi, Vanesa Diyan; Ferdiansyah, Ferdiansyah; Septiani, Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to determine the influence of capital structure, dividend and cash holding policies on company value in property and real estate companies listed on the Indonesian Stock Exchange (BEI) for the 2018-2022 period. This type of research is quantitative associative using secondary data obtained from www.idx.co.id and from the websites of each company. Sampling in this research used a purposive sampling method and 6 property and real estate companies were obtained as samples. The analysis technique used is panel data regression analysis using the E-views 12 tool. The results of this research show that capital structure has an effect on company value, but dividend and cash holding policies have no effect on company value. The results of this research also show that capital structure, dividend policy and cash holding simultaneously influence company value.